Predictor of Major Adverse Cardiac Event (MACE) in Acute Coronary Syndrome (ACS) patients: A Scoping Review - Anita Sukarno; Utari Yunie Atrie; Budi Mulyana; Dewi, Ratna (International Journal of Nursing and Health Services (IJNHS), 2022)
Introduction: Acute Coronary Syndrome (ACS) is a contributor to morbidity and mortality rates every year. The cause of death in ACS is a complication known as a MACE. However, it has not been known what can trigger the occurrence of MACE after post-ACS treatment. Objective: This study aimed to review and assess conditions that could predict the occurrence of MACE after treatment of ACS patients. Method: We conducted literature on articles between 2016-2021 with four databases: PubMed, Science Direct, CINAHL, and the search engine, namely Google Scholar. The design used is a scoping review. Five independent reviewers analyzed the inclusion and exclusion criteria. The researchers drew data from each article: author, year, region, purpose, design, related factors, and results. Furthermore, the researchers used PRISMA to compile the manuscript. There were 30 articles included in the analysis. One thousand articles were obtained through a basic data search based on the PRISMA flowchart, and after finding the manual, 30 studies were identified. Researchers selected relevant articles, namely predictors associated with MACE after treatment of ACS patients. Result: The results found that the predictors associated with MACE in ACS were comorbidities, adherence to hemodynamics medication, clinical parameters, the severity of atherosclerosis, increased cardiac disease assessment scores, and psychosocial disorder.